Strategies to prevent and manage running-related knee injuries: a systematic review of randomised controlled trials - Alexander, J. L. N.; Culvenor, A. G.; Johnston, R. R. T.; Ezzat, A. M.; Barton, C. J. (British Journal of Sports Medicine, 2022)
Objective: To evaluate the effectiveness of interventions to prevent and manage knee injuries in runners.